One last scuffle before we cherish brand love forever. (November 2019) - Junaid, Muhammad; Hussain, Khalid; Hou, Fujun
The extant literature on brand love lacks appraisal of theories and discourse on the conceptualizations of brand love. This work differentiates these conceptualizations, categorizes in three mutually exclusive forms, and labels as perfect two-way love, imperfect two-way love, and perfect one-way love .